Caracterização epidemiológica dos pacientes internados em um hospital de tuberculose do Estado de São Paulo, Brasil - Junior, Rodolpho Telarolli [UNESP]; Loffredo, Leonor de Castro Monteiro [UNESP] (My University, 2015)
The objective of this work was to characterize, from the epidemiological, demographic and social point of view, patients with tuberculosis hospitalized at a hospital in the state of São Paulo, Brazil. Data sources were obtained from the hospital records of 114 patients who were discharged from the hospital in 2010. Of the 114 patients, 82.5% were men and 80% were between 20 and 49 years old. Only 16.7% were married or cohabiting; the remaining lived alone. In terms of schooling, 85.2% had completed elementary school, 9.7% of patients were homeless, and only 3.5% were working before being hospitalized. Hospitalization between 1 and 6 months (61%) predominated, as well as the number of patients who were discharged because they were cured or discharged to continue their treatment on an outpatient basis. (69.4%) The mortality rate among the patients was 7.9% and the co-morbidity of TB/HIV was 9.7%. Only one case was not of pulmonary tuberculosis and 5.3% were multidrug resistant. In relation to co-prevalence, alcoholism (71.0%), drug addiction (15.8%), and hepatitis C (12.3%) predominate. The hospitalization of patients with tuberculosis has little to do with the disease; it is mainly associated with the lifestyles of the patients, such as the use of illicit drugs and alcohol, the absence of residency and other factors. Mortality was higher in this group of people compared to those who had received outpatient treatment. This situation can be addressed with an early diagnosis of the disease through the primary health care network.
Epidemiological characterization of patients at a tuberculosis hospital in the state of São Paulo, Brazil
Keywords: Epidemiology; Hospitalization; Risk factors; Tuberculosis